The dorsal pancreatic artery: A meta-analysis with clinical correlations - Rousek, Michael; Whitley, Adam; Kachlík, David; Balko, Jan; Záruba, Pavel; Belbl, Miroslav; Nikov, Andrej; Ryska, Miroslav; Gürlich, Robert; Pohnán, Radek (Pancreatology, 2022)
BACKGROUND/OBJECTIVES: The dorsal pancreatic artery is the main artery of the body and tail of the pancreas. Its origin and branching is highly variable. The aim of this study was to perform a meta-analysis to generate pooled prevalence data on the presence and origin of the dorsal pancreatic artery. Clinically important aspects of the dorsal pancreatic artery were summarised during the literature review. METHODS: Major medical databases were searched. Data on the presence and point of origin of the dorsal pancreatic artery were extracted and quantitatively synthesised. The obtained data of anatomical based studies and computed tomography based studies were statistically analysed. RESULTS: In total, 30 studies, comprising 2322 anatomical and computed tomography based cases were included. The dorsal pancreatic artery was present in 95.8% of cases. It originated from the splenic artery in 37.6% of cases, common hepatic artery in 18.3% of cases, coeliac trunk in 11.9% of cases and the superior mesenteric artery in 23.9% of cases. Other rare origins were present in 2.77% of cases. Multiple dorsal pancreatic arteries were found in 1,7% of cases. There was no significant difference in the presence or origin of the dorsal pancreatic artery between anatomical and computed tomography based studies. CONCLUSION: The dorsal pancreatic artery is present in the vast majority of cases. Its origin and branching are highly variable. Multiplicity of the dorsal pancreatic artery is infrequent.
Keywords: pankreas; počítačová rentgenová tomografie; Pancreas; Celiac Artery; arteria mesenterica superior; arteria lienalis; Splenic Artery; Humans; Mesenteric Artery, Superior; lidé; Tomography, X-Ray Computed; arteria coeliaca